A Comparative Study of Stone Clearance Rates in Retrograde Intrarenal Surgery (RIRS) for Kidney Stones Above and Below 5 cm in Size (Medical Forum Monthly, 2024)
Objective: To analyse stone clearance rates in RIRS patients with stones larger than 1.5 cm compared to those with smaller stones, providing insight into RIRS's potential as a preferred approach for kidney stone management.Study Design: Retrospective cohort studyPlace and Duration of Study: This study was conducted at the Urology department of The kidney Centre Postgraduate Training Institute from the time period of May 2023 to June 2024.Methods: 151 patients who underwent RIRS at The Kidney Centre Postgraduate Training Institute over a period of one year. Cohorts: - Group A: Stones <1.5 cm. Group B: Stones ≥1.5 cm. Data Analysis: SPSS, p-value ≤0.05 considered significant.Results: Complete Clearance in Group A: 79.6% and Group B: 60.5%. Residual Stone Fragments Less than 4 mm on X-ray or Ultrasound Group A: 16.7% and Group B: 34.9%.Conclusion: RIRS, in selected cases, can be effective for larger stones (≥1.5 cm) with comparable clinically significant clearance. -Advantages over PCNL include minimal invasiveness, faster recovery, lower morbidity.